Farmers' perceptions and knowledge on chrysanthemum pests and its management in West Java, Indonesia. Issue 1 (March 2021) - Hutapea, D; Hidayat, P; Dadang; Sartiami, D
Abstract: Sustainable pest management on greenhouse crops should be based on farmers' perspectives, obstacles, and technical knowledge. A survey of 41 farmer households that producing chrysanthemum was conducted to identify pest problems that were considered most important by farmers and identify knowledge of insecticides used in pest management. The respondents were chosen purposively based on easiness encountered in the greenhouse from the three districts of chrysanthemum production centers (Bogor, Cianjur, and Sukabumi) in West Java Province. The data were collected through group discussion techniques and individual interviews using a questionnaire and then analyzed by descriptive statistical methods. The results showed that among the pests, mostly farmers (90%) perceived that thrips were the main pest. Regarding to control pests, all farmers used insecticides thrice a week, and the most insecticide groups applied were avermectin, cyromazine, organophosphate, diafenthiuron, neonicotinoid, and pyrethroid. The determination of insecticides was based on farmers' own past experiences, other farmers' experiences, and suggestions from pesticide retailers. Even though the pesticides were implemented intensively, most farmers (78%) were unsatisfied with the effectiveness of control. Understanding farmers' knowledge dealing with pests and their impacts is baseline information to develop sustainable pest management on chrysanthemum under greenhouse conditions.